PENINGKATAN KOMPETENSI ISLAMI BERWAWASAN LINGKUNGAN MAHASISWI UNIVERSITAS MUHAMMADIYAH PALANGKARAYA MELALUI KULIAH KERJA NYATA - Ady Ferdian Noor; Bulkani Bulkani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Student competency is a skill that must be developed through the Community Service Program (KKN). KKN Muhammadiyah University of Palangkaraya carried out according to the Master Plan Development of PkM and modified with the Motto of Muhammadiyah University of Palangkaraya: